Emerging nanomedicine applications and manufacturing: progress and challenges. (March 2016) - Sartain, Felicity; Greco, Francesca; Hill, Kathryn; Rannard, Steve; Owen, Andrew
APS 6th International PharmSci Conference 2015: 7–9 September 2015 East Midlands Conference Centre, University of Nottingham, Nottingham, UK As part of the 6th APS International PharmSci Conference, a nanomedicine session was organised to address challenges and share experiences in this field. Topics ranged from the reporting on latest results and advances in the development of targeted therapeutics to the needs that the community faces in how to progress these exciting proof of concept results into products. Here we provide an overview of the discussion and highlight some of the initiatives that have recently been established to support the translation of nanomedicines into the clinic.